Clinical characteristics and identification of a novel TGFB1 variant in three unrelated Chinese families with Camurati‐Engelmann disease. Issue 5 (21st March 2022) - Tao, Xiao‐Hui; Yang, Xing‐Guang; Wang, Zi‐Yuan; Xu, Yang; Lin, Xiao‐Yun; Xu, Tian; Zhang, Zhen‐Lin; Yue, Hua
Abstract: Background: To investigate the clinical characteristics and molecular diagnosis of Camurati‐Engelmann disease (CAEND) in Chinese individuals. Methods: We recruited six patients aged 14 to 45 years in three unrelated families with CAEND, including five females and one male. Clinical manifestations, biochemical tests, and radiographic examinations were analyzed. The TGFB1 gene variants were further identified by Sanger sequencing. In addition, one female patient was followed up for 5 years. Results: The onset age of the patients ranged from 1 to 6 years. All of them had family histories and consisted of an autosomal dominant inheritance pattern. Gait disturbance, fatigue, progressive bone pain, muscle atrophy, and weakness were the main complaints. Laboratory examinations revealed that the inflammatory markers were at high levels, in addition to the increased bone metabolism indicators. The thickened diaphysis of long bones and the narrowed medullary cavity was observed by radiography. Furthermore, bone scintigraphy detected abnormal symmetrical radioactive concentrations in the affected regions of bone. Sanger sequencing identified a missense heterozygous variant in exon 4 of the TGFB1 gene in families 1 and 2, resulting in Arg218Cys, which confirmed CAEND. Moreover, one novel variant c.669C > G in exon 4 of the TGFB1 gene harboring Cys223Trp was detected in family 3. Subsequent bioinformatics software predicted that the novel variant was pathogenic. Of interest, III:2 in family 3 experienced heart valve defects and tachycardia at birth, which had never been reported in CAEND patients before. Moreover, the response to drug treatment is also full of contradictions and is worthy of further study. Conclusion: Besides the typical CAEND manifestations, the new phenotypic characteristics of tachycardia and heart valve defects were first reported in one woman carrying the novel variant p.Cys223Trp in TGFB1 the gene. In addition, we demonstrated that increased bone metabolism indicators and inflammatory markers may possess auxiliary diagnosis for CAEND. Abstract : To investigate the clinical characteristics and molecular diagnosis of Camurati‐Engelmann disease (CAEND) in China. In addition to the typical CAEND manifestations, tachycardia and heart valve defect were firstly reported in one girl carried the novel variant p.Cys223Trp in TGFβ1 gene, whereas whether the observed symptom was related to CAEND remains to be further investigated. In addition, we demonstrated that increased bone metabolism indicators and inflammatory markers may possess auxiliary diagnosis for CAEND.